Pengaruh Proaktif, Inovatif, Keberanian Mengambil Resiko terhadap Kinerja pada Pelaku UMKM di Kota Makassar dengan Strategi sebagai Variabel Moderasi - Khairin Magfira; Farild, Miftha (Universitas Islam Negeri Alauddin Makassar, Indonesia, 2024)
Micro, Small and Medium Enterprises (MSMEs) are one of the most important pillars in the Indonesian economy. MSMEs are one of the businesses that are currently in the spotlight because they have a strategic role in opening up jobs, new businesses and contributing greatly to increasing gross domestic product. This study was conducted to determine the Influence of Proactive, Innovative, Courage to Take Risks on Performance in MSME Actors in Makassar City with Strategy as a Moderating Variable. Keywords: Micro, Small and Medium Enterprises (MSMEs), Productive, Innovative, Courage to Take Risks, Performance, Strategy